A new species and depth record of bopyrid (Crustacea, Isopoda) from a squat lobster in the Kuril-Kamchatka Trench - Williams, Jason D.; Boyko, Christopher B.; Marin, Ivan N. (European Journal of Taxonomy, 2020)
The branchial parasitic isopod Pleurocryptella altalis sp. nov. (Bopyridae: Pseudioninae) is described from the squat lobster host Munidopsis petalorhyncha Baba, 2005. The new species is morphologically similar to Pleurocryptella formosa Bonnier, 1900 and P. wolffi Bourdon, 1972b but can be distinguished based on male characters (differences in head, pleon and uropods) and female characters (differences in barbula, pleopods and pleotelson). The parasite specimens (a female and male pair) were collected with the squat lobster host at a depth of 5060–5130 m from the Kuril-Kamchatka Trench, representing the deepest record for any of the 850+ described bopyrid isopod species and for any record of an infested host. Dichotomous identification keys to females and males of Pleurocryptella species and subspecies are provided.